2003
DOI: 10.1093/annonc/mdg071
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensitivity and p53–Bax pathway-mediated apoptosis in patients with uterine cervical cancer

Abstract: Chemosensitivity in cervical cancer may be associated with apoptosis via the p53-Bax pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 32 publications
4
27
0
1
Order By: Relevance
“…Interestingly, concordance has been seen with HPV16 prevalence and p53 up-regulation in the tumors. It seems that in HPV positive tumors, at least one of the p53 alleles is in wild type state and its up-regulation might activate the G1/S checkpoint, along with induction of apoptosis of the differentiated cells, as evident from previous studies (Sultana et al, 2003;Mitra et al, 2007). This induction might be due to the up-regulation of BAX by p53, as concordance has been seen between expressions of these proteins in post-therapy tumors.…”
Section: Discussionsupporting
confidence: 53%
“…Interestingly, concordance has been seen with HPV16 prevalence and p53 up-regulation in the tumors. It seems that in HPV positive tumors, at least one of the p53 alleles is in wild type state and its up-regulation might activate the G1/S checkpoint, along with induction of apoptosis of the differentiated cells, as evident from previous studies (Sultana et al, 2003;Mitra et al, 2007). This induction might be due to the up-regulation of BAX by p53, as concordance has been seen between expressions of these proteins in post-therapy tumors.…”
Section: Discussionsupporting
confidence: 53%
“…This association between tumor proliferative activity and response to chemotherapy has been reported in breast cancer (27,28). Additionally, in cervical cancer, Sultana et al (29) reported that high expression of Ki-67 in preoperative biopsies was associated with the clinical response to platinum-containing neoadjuvant chemotherapy and improved prognosis. On the other hand, Costa et al (30) reported that there was no correlation between Ki-67 expression and clinical response to neoadjuvant chemotherapy or prognosis.…”
Section: Hdra Developed By Hoffman Et Almentioning
confidence: 54%
“…However, contradictory results have also been found in terms of Bcl-2 expression and patient prognosis (42)(43)(44)(45)(46)(47)(48)(49). Furthermore, in one study, no significant association was observed between Bcl-2 expression and the clinical effects of neoadjuvant chemotherapy (29). Thus, the association between Bcl-2 expression and chemosensitivity/radiosensitivity or prognosis has not been precisely defined.…”
Section: Hdra Developed By Hoffman Et Almentioning
confidence: 98%
See 1 more Smart Citation
“…Bcl-2, an anti-apoptotic protein, is an oncogene that inhibits radiation-or chemotherapy-induced apoptosis (30). Cervical cancers with Bcl-2 expression have been reported to exhibit radiation resistance and poor prognosis (31,32). Bax is a member of the Bcl-2 family and serves a role in enhancing apoptosis (33).…”
Section: Discussionmentioning
confidence: 99%